The Superiority Complex of Drea in the Do Revenge Movie Using Adler’s Theory - Lolang, Benedicta Viorell; Widyaningrum, Agnes (LPPM Universitas Bumigora Mataram, 2025)
This study examines the superiority complex’s behavior in